(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Celebrity endorsements is a popular form of marketing whereby companies hire well known celebrities to promote their products. Big scale celebrity endorsements entice endorsement fees in millions of dollars. However, there exists limited literature discussing this theme of celebrity endorsements for the Indian footwear industry. The said industry has been growing at a rapid rate and is witnessing involvement of celebrity endorsements at a large scale. Therefore, this study has tried to perform an empirical analysis which can be used by Indian footwear industry for strategizing their celebrity endorsements campaigns. It was found that the Indian footwear industry is unable to make profitable gains from the amount that it invests in the celebrity endorsements. This result was measured considering that the footwear industry hires a celebrity based upon his / her attractiveness and credibility. However, attractiveness of the celebrity has no significant contribution in enticing consumer interests or consumer purchase of the footwear product. It has been suggested that Indian footwear companies need to carefully select a celebrity who can be suitably matched to the underlying product so as to maximize the efficiency of the celebrity endorsement campaign.